A Study of Intellectual Capital and Its Supply Chain Strategy for Business Performance in Small Medium Enterprise (SMEs) - Widiartanto, Widiartanto; Eko Wahyudi, Fendy; Zarkasyi Rahman, Amni; Shinta Dewi, Reni; Saputra, Jumadil (International Journal of Supply Chain Management, 2020)
Intellectual capital is one of important activity for organizations which want to be efficient on the market and obtain a sustainable competitive advantage. However, most company only measure and create company value based on tangible assets rather than intangible assets. In conjunction with the present issue, this investigation focuses on intangible assets (intellectual capital) in Small Medium Enterprise (SMEs) and its supply chain strategy for business performance. This study is designed using a qualitative approach. A total of 30 entrepreneurs from the three largest Batik industries in Central Java, consist of Lasem-Rembang, Pekalongan and Laweyan Solo has participated in this study. The data collection technique is using observation, interview and some relevant reference such as reports, books and journals. The results of the analysis showed that the intangible assets (intellectual capital) are a strategic way to improve the performance of SMEs. Also, this study identified that the intellectual capital consists of human capital, spiritual capital, organizational capital, consumer capital and social capital. In conclusion, as intangible assets (intellectual capital) is a knowledge-based view that can create value and increase organizational performance. Also, the concept of intellectual capital is relatively new, especially for SMEs, so the subjectivity of perception given is still very high.Keywords— Intangible and tangible assets, intellectual capital, supply chain strategy, organizational performance